What Germany's medium-term fiscal plan means for Europe - Jeromin Zettelmeyer; Zsolt M. Darvas; Lennard Welslau (Bruegel, 2025)
Germany's July 2025 medium-term fiscal-structural plan exposes the tension between raising public investment in a low-risk country and the requirement in European Union fiscal rules for member state debt to comply with the 60 percent of GDP public debt ratio benchmark. Germany's plan seeks to reconcile this tension by adopting overly optimistic GDP growth and inflation assumptions, and by proposing a large, backloaded fiscal adjustment. The European Commission endorsed the plan without rigorously assessing these assumptions. Under more realistic economic assumptions, both the budget deficit and the public debt would be significantly higher than the plan's projections. Rather than beginning to fall by the end of the allowed seven-year adjustment period, German debt will likely continue to rise, even if Germany keeps its promise to sharply reduce expenditure growth after 2026. This outcome would be inconsistent with the EU fiscal framework, but not threaten the sustainability of German public debt, as the fiscal adjustment required to stabilise the debt would remain feasible. Germany will likely ultimately deliver the necessary consolidation, but over a longer period than foreseen by the EU rules. However, the Commission's approval of the German plan establishes a precedent that could undermine the credibility of the EU's fiscal framework. Other EU countries may cite the Commission's leniency to justify higher expenditure growth not grounded in sound economic assumptions during the next round of national fiscal plan submissions in 2028, or even earlier through mid-term revisions. To prevent such an outcome, EU fiscal rules should be adjusted. The best option would be to permit low-risk countries with credible investment plans longer adjustment periods than the current seven-year maximum. Such a reform would result in a coherent system that ensures both debt sustainability and allows more public investment. The second-best option would be to raise the Treaty's debt reference value from 60 percent to 90 percent of GDP. If neither proves politically feasible, technical adjustments to the debt sustainability analysis could still be made, but these would yield only marginal improvements.
Keywords: 330